The Impact Of The Waste Bank Program On The Income Level Of Waste Bank Customers (Case Study at the Eka Jaya Waste Bank, Sememi Village, Benowo District, Surabaya City) - Risa Valentine; Muhammad Yasin (Kampret Journal, 2023)
One of the major breakthroughs in waste management in Indonesia is the waste bank program. Through this program, it is formed in people's minds that waste is something that is useless and is simply thrown away, converted into something that also has value and price. Through the waste bank, people can save waste, which can then generate money within a certain period of time. Research using descriptive research methods with quantitative analysis. This study aims to find out how the impact of the waste bank program on the socio-economic community in Sememi Village, Benowo District, Surabaya City. Impact is defined as an influence that brings both positive and negative consequences. In this case the impact is aimed at the socio-economic life of the community at the Eka Jaya Garbage Bank, Sememi Village, Benowo District, Surabaya City. Based on the results of data analysis, it was concluded that there was a positive impact on the socio-economic life of the people in Sememi Village, Benowo District after the construction of the Garbage Bank. This is indicated by an increase in people's income, although it is small, it provides significant benefits for the community. Not only income has increased, but health and better social interaction among people, most importantly, a cleaner environment has also increased from time to time